Practical Guidelines: How to Ask for a Letter of Recommendation (Out of Print) - Susan Kies (Association of American Medical Colleges, 2005)
Abstract This resource provides students with step-by-step instructions on approaching faculty members for letters of recommendation and guides them on providing succinct and relevant information to faculty members. This way, faculty can focus on the preparation of strong letters of recommendation instead of dealing with logistics in writing these letters when the students apply for various opportunities. Likewise, when students ask for a letter of recommendation, this resource may be provided to them first. This is an effective and practical tool that may be used frequently throughout the year.